O efeito do fogo e geadas no Cerrado sobre o mutualismo entre a planta extranectarífera Ouratea spectabilis (Mart.) Engl. (Ochnaceae) e formigas. - Porto, Gabriela Fraga (2022)
The Cerrado is a savannah with great diversity exposed to alterations such as fire and frosts, these distubances act as an important force and evolution for local species and can occur due to natural or not. Frosts and fires can trigger changes in attributes that affect biodiversity at different levels of interaction and with the intensification of climatic extremes studies to understand how these phenomena affect ecological relationships are of paramount importance for the biodiversity of natural ecosystems. Thus, this study aimed to understand the effects of fire and frost on a plant with extrafloral nectaries (EFNs), the Ochnaceae Ouratea spectabilis and their interactions. To this end, we investigate the following issues after fire and/or frost: 1) the regrowth time of O. spectabilis; 2) the variation in the abundance and diversity of ants and associated herbivores; 3) and the results of biotic interactions (plant with EFNs-ant-herbivore). The central questions to be answered were: i) if recovery time of plants after frost and after frost followed by fire were different? ii) did these disturbances affect the fauna of ants and herbivores associated with O. spectabilis differently? iii) did the protective behavior of ants associated with O. spectabilis vary between species under the effect of frost and under the effect of frost and fire? iv) plants with re-sprouting EFNs suffer less damage by herbivores compared to plants without NEFs due to the biotic protection provided by the ants? v) is there an association between ant diversity and abundance and plant herbivory rates after fire and after frost and fire? The results showed that fire accelerated the regrowth of O. Spectabilis and the plant without EFNs used as a model, Aspidosperma tomentosum (Apocynaceae), in a Cerrado previously affected by frost. Regrowth in plants with EFNs attracted ants that proved to be efficient in removing herbivores, significantly reducing foliar herbivory rates in this species, compared to the species without EFNs, or when ant access was prevented through experimental manipulation. The fauna of ants and herbivores were low post-disturbances, with frosts causing a reduction of herbivores and ants. Furthermore, the richness and diversity of ants were higher in the area that suffered the effect of frost and subsequent fire, compared to the area that suffered only the effect of frost. This study suggests that fire is important in restoring ecological interactions in the Cerrado, affecting plants, ants and herbivores less negatively than frost.